GEJOLAK HARGA KOMODITAS PANGAN INTERNASIONAL : DAMPAK DAN IMPLIKASI KEBIJAKAN BAGI KETAHANAN PANGAN INDONESIA - Ratna Winandi Asmarantaka; Rina Oktaviani (Jurnal Agribisnis dan Ekonomi Pertanian, 2009)
The volatility of international food price has become a challenge for food development in Indonesia. General Equilibrium Economic Model was used to analyze the effect of international food price volatility to the Indonesian Macro Economic Condition, besides it also captured the ability from the chosen policy scenario and the increase of productivity which stated to analyze the national food security. The simultaneous equation model (2 SLS) was used to analyze the farm household economic characteristics (RTP), the interaction among production, consumption, income, saving, and the impact which caused from main output price changing (dominant) to RTP food security. The increase in international food price caused the increase in GDP, consumption, wage, and real price. Meanwhile, on the commodities, the effect on production, export and import varied. At the household level, the increase in commodity price would increase consumption, wage and income. Therefore the increase in international price would have positive effect on food security.